Analysis of CD4+ CD8+ double-positive T cells in blood, cerebrospinal fluid and multiple sclerosis lesions - Waschbisch, Anne; Sammet, Laura; Schröder, S.; Lee, D. -H.; Barrantes-Freer, A.; Stadelmann, C.; Linker, Ralf (Clinical and Experimental Immunology, 2014)
T cells with a CD4(+) CD8(+) double-positive (DP) phenotype are present in small numbers in the peripheral blood of healthy humans and may have anti-viral capacities. Here we investigate numbers and function of DP T cells in patients with relapsing-remitting multiple sclerosis (MS), either treatment-naive or under therapy with natalizumab. Flow cytometry analysis revealed that frequencies of circulating DP T cells in treatment-naive and natalizumab-treated MS patients are comparable to healthy controls. These cells have a memory phenotype with cytotoxic potential, express high levels of CD49d and are similarly functional in treatment-naive as well as natalizumab-treated MS patients. DP T cells were enriched in the cerebrospinal fluid, but do not invade acutely inflamed MS lesions. In conclusion, DP T cells are functional in MS and may play a role in the immune surveillance of the central nervous system, but do not display functional impairment under natalizumab therapy.
EVALuna2:22346